International perspectives: favorable winds that blow from Spain and experience with innovation seminars in primary health care (SICSP) (Portuguese Journal of Family Medicine and General Practice, 2009)
INTERNATIONAL PERSPECTIVES; THE FAVOURABLE WINDS BLOWING FROM SPAIN AND THE EXPERIENCE OF THE PRIMARY HEALTH CARE INNOVATION SEMINARS The primary care innovation seminars are a unique initiative in the european stage of primary health care. It is organized jointly by three spanish organizations and coordinated by a general practitioner. The seminars foster the analysis of the latest trends and innovations in terms of the organization of health care services, clinical research, as well as the main issues that will embody family medicine in the 21st century. This initiative is of interest to portuguese primary care physicians and trainees, since the contact with this initiative caters for a considerable personal gain in terms of inherent discussion, production of knowledge and interaction with a dynamic spanish multidisciplinary network of primary health care professionals.
Keywords: Innovation; Primary Care; Network; Seminars; Spain